To divide \( -\frac{4}{9} \) by \( \frac{4}{7} \), we can multiply \( -\frac{4}{9} \) by the reciprocal of \( \frac{4}{7} \):
\[
-\frac{4}{9} \div \frac{4}{7} = -\frac{4}{9} \times \frac{7}{4}
\]
Now, multiply the fractions:
-
Multiply the numerators:
\[
-4 \times 7 = -28
\]
-
Multiply the denominators:
\[
9 \times 4 = 36
\]
Putting it all together, we have:
\[
-\frac{4}{9} \div \frac{4}{7} = -\frac{28}{36}
\]
Now, simplify \( -\frac{28}{36} \):
- The greatest common divisor of 28 and 36 is 4.
So, we can simplify:
\[
-\frac{28 \div 4}{36 \div 4} = -\frac{7}{9}
\]
The correct response is:
−7/9